The chemical analysis of Lebanese olive oil and the influence of oil enriched diet on Plasma Lipid profile in rats. (c2002) - Zarikian, Karen Awadis (2002)
In the second half of this century, emphasis on diet related diseases increased as the major cause of mortality shifted from infections to chronic diseases. Cardiovascular disease (CYD) has been the number one killer in the United States since 1900. According to the American Heart Association 2002 Heart Statistical Update, one death is reported from CYD every 33 seconds. Atherosclerosis is the major underlying cause of coronary heart disease. Diet rich with cholesterol and saturated fat is believed to increase plasma levels of total and low density lipoprotein cholesterol, the primary lipoprotein mediating atherosclerosis. According to the 200 I guidelines of the National Cholesterol Education Program Panel III, dietary treatment must proceed pharmacological therapy in hyperlipidemic patients for a three month period. It has been hypothesized that vegetable oils such as olive oil, canola oil, soybean oil, are major sources of monounsaturated and polyunsaturated fatty acids and that they have more favorable effects on the distribution of cholesterol. Olive Oil is the major fat used in the Mediterranean diet. Different environmental factors and harvesting techniques influence the chemical composition of olive oil. The primary objective of this study was to identify the fatty acid, sterol and squalene concentrations and acidity in the Lebanese olive oil prepared by the cold press and automated methods. Another objective was to observe the influence of a ten week olive oil enriched diet on the plasma lipid profile, insulin levels, coagulation time and Apolipoprotein B 100 and B 48 levels in rats. Olive oil samples were obtained from 11 different Lebanese areas. The identification of the fatty acids, sterols and squalene was performed on gas chromatography mass spectrometry (GeMS) and the acidity was identified by titration. In the second phase of the study, 42 rats were divided into three groups and fed for J 0 weeks the following diets: a) normal rat diet, b ) diet enriched with olive oil prepared by the automated method and c ) diet enriched with oil prepared by the cold press method. The oil of black olives prepared by the automated method from Beshaale (Northern Lebanon) contained the highest percentage of oleic acid and sterol concentration whereas the oil from Zrarieh (southern Lebanon) contained the least. On the other hand, the highest squalene concentration was found oil obtained from green olives brought from Beshaale. The most acidic oil was the one obtained from Koura, Kfar Akka (northern Lebanon), prepared by the automated method. Following ten week low fat verses high fat diet, no significant difference was observed among the various groups in lipid profile, insulin and Apo B 100 & 48 levels. There was a decrease in clotting time in the group fed the automated olive oil compared to the control and an increase in the clotting time in the group fed cold press olive oil compared to the automated. These findings suggest possible altered fat metabolism in rats. Further studies in humans might yield better conclusive results. In conclusion, the present study was able to identify the chemical composition of Lebanese olive oil in terms of fatty acids, sterols and squalene content. In addition, the increased acidity in some of the consumed olive oils is of great concern. In order to observe difference in lipid profile, well designed dietary experiments in humans is needed, because the squalene metabolism in rats is different than in humans.